Simultaneous Determination of Hydrochlorothiazide in Combination with Some Antihypertensive Drugs in The Presence of Its Main Impurities in Pure Form and Pharmaceutical Formulations - Salem, Maissa Y.; Hassan, Nagiba Yehia; Fayez, Yasmin Mohamed; ElSabour, Samah Abd; Ali, Enas Shaaban (Current Pharmaceutical Analysis, 2020)
Background: Hydrochlorothiazide (HCTZ) is potent diuretic that is used alone or in combination with other drugs such as labetalol (Lab) (mixtures ) or nebivolol (Neb) (mixtures ) to control moderate to sever hypertension. Introduction: This paper demonstrates the establishment of different validated spectrophotometric and chemometric methods for simultaneous estimation of these mixtures in pure form and pharmaceutical formulations in the presence of HCTZ related impurities in quality control laboratories. Methods: (A) Derivative method (D3) of Lab and HCTZ and its related impurities at 245.3nm and 278.5nm respectively, (D1) of Neb and HCTZ at 294.2nm and 282.2nm, respectively. (B) First derivative of ratio spectra method (DD 1) of Lab at 244.3nm, HCTZ at 261.2nm and 275.4nm, while at 294nm for Neb and 269.4nm for HCTZ. (C) Ratio difference method which depends on measuring the distinction between the amplitudes of ratio spectra at 240nm and 288.3nm for Lab and at 270.1nm and 277.4nm for HCTZ for mixture while at 290.4nm and 299.2nm for Neb and at 232.2nm and 254nm for HCTZ for mixture . (D) Mean centering of ratio spectra (MC) and (E) partial least squares regression (PLS) and principal component regression (PCR). Results: These methods were applied over concentration ranges of 10-100 μg/ml, 10-75 μg/ml and 2.5- 25 μg/ml of Lab, Neb and HCTZ, respectively. Methods were validated according to ICH guidelines and statistical comparison of results of reported and proposed methods revealed no difference. Conclusion: The methods were successfully used for the frequent analysis of selected mixtures in quality control laboratories.
Keywords: spectrophotometry